PENGENALAN INVESTASI DI PASAR MODAL PADA PELAKU UMKM CIKARANG PUSAT - Nurjanah, Rina; Andriyani, Meli; Kosim, Muhammad; Nurastuti, Preatmi; Istiqomah, Anisah (Aptekmas Jurnal Pengabdian pada Masyarakat, 2024)
This activity focuses on introducing investment in the capital market to Micro, Small and Medium Enterprises (MSMEs), especially those who are members of the Central Cikarang MSME Forum. The micro and small business groups that are the focus involve culinary, convection, souvenir traders and others. Most of these MSME players have a lack of knowledge in the financial sector, especially regarding investment. Therefore, the aim of this activity is to increase their understanding of investment, especially in the capital market context. This is important so that they can manage their funds wisely and avoid mistakes in investment management. Training is carried out using presentation methods, question and answer sessions, and discussions to facilitate understanding and absorption of the material provided. The main focus of the training is to provide guidance on how to make good investments, especially regarding stock investments in the capital market. The results of the activity provide real benefits for MSEs and increase knowledge and understanding regarding investment in the capital market. The existence of the application makes it easier for participants to make investments anytime and anywhere. Participants were very enthusiastic about this activity and hoped that this activity could be held sustainably.